CFTR is involved in the regulation of glucagon secretion in human and rodent alpha cells - Edlund, Anna (Sci Rep, 2017)
Glucagon is the main counterregulatory hormone in the body. Still, the mechanism involved in the regulation of glucagon secretion from pancreatic alpha cells remains elusive. Dysregulated glucagon secretion is common in patients with Cystic Fibrosis (CF) that develop CF related diabetes (CFRD). CF is caused by a mutation in the Cl(−) channel Cystic fibrosis transmembrane conductance regulator (CFTR), but whether CFTR is present in human alpha cells and regulate glucagon secretion has not been investigated in detail. Here, both human and mouse alpha cells showed CFTR protein expression, whereas CFTR was absent in somatostatin secreting delta cells. CFTR-current activity induced by cAMP was measured in single alpha cells. Glucagon secretion at different glucose levels and in the presence of forskolin was increased by CFTR-inhibition in human islets, whereas depolarization-induced glucagon secretion was unaffected. CFTR is suggested to mainly regulate the membrane potential through an intrinsic alpha cell effect, as supported by a mathematical model of alpha cell electrophysiology. In conclusion, CFTR channels are present in alpha cells and act as important negative regulators of cAMP-enhanced glucagon secretion through effects on alpha cell membrane potential. Our data support that loss-of-function mutations in CFTR contributes to dysregulated glucagon secretion in CFRD.